Hierarchical Modular Architecture Enabling Intelligent Dynamic Thermal Management and Superior Electromagnetic Interference Shielding - Xuan, Qi‑Fan; Zhao, Pei‑Yan; Peng, Hualong; Zhang, Shan; Cai, Bo; Niu, Fang‑Yu; Koo, Martin C.; Sun, Xiao‑Bo; Jiang, Xiangyu; Wang, Guang‑Sheng (Nano-Micro Letters, 2026)
Integrated wearable thermal management technologies have greatly enhanced human adaptability to complex environments. However, conventional thermal management strategies, which lack environmental risk perception and stable human–machine interaction, are increasingly inadequate for ensuring personal health. Here, we introduce a hierarchical modular design strategy to develop a wearable intelligent thermal management film with robust electromagnetic interference (EMI) shielding capabilities. A sensitive biomimetic serpentine dual-mode temperature–humidity sensing module is coupled with a low-power electro-/photothermal conversion module to enable intelligent thermal regulation. The resulting thermal management system offers stable and sensitive front-end temperature–humidity monitoring, alongside low-power electrothermal (51.79 °C at 1.5 V) and photothermal (56.38 °C at 45.51 mW cm−2) temperature regulation capabilities. Additionally, the system exhibits outstanding EMI shielding performance, with an EMI SE/t value of 1600 dB mm–1 at a thickness of just 35 μm, ensuring stable signal transmission. The hierarchical modular design enables functional allocation with higher, thereby optimizing material performance while enhancing the decoupling and synergistic effects between different functionalities. These findings provide a scalable and practical pathway for the multifunctional integration and performance optimization of next-generation flexible wearable electronic composites. Highlights: 1 Hierarchical modular architecture for integrated design and functional optimization. 2 Development of an intelligent monitoring and feedback-driven thermal management system, providing not only stable and sensitive front-end temperature and humidity monitoring, but also low-power thermoelectric (1.5 V, 51.79 °C) and photothermal (45.51 mW cm-2, 56.38 °C) dual complementary temperature control capabilities for the back end. 3 Multiscale and scalable conductive gradient for exceptional electromagnetic interference shielding performance (35 μm, 1600 dB mm-1), ensuring stable signal transmission across the system.